Some Results on Generalized Sasakian-Space-Forms: U.C. De, Avijit Sarkar - Team, Support (Thai Journal of Mathematics, 2010)
The object of the present paper is to study locally -symmetric generalized Sasakian-space-forms and generalized Sasakian-space-forms with -recurrent Ricci tensor. Such space-forms with three-dimensional quasi-Sasakian structure are also considered.